2018
DOI: 10.1177/1469066718756801
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of acetylated histidine b1-ion structure: A competition between oxazolone and side chain imidazole moiety

Abstract: The detection of post-translational modifications of proteins is an important comprehensive research area. Over the years, proteomic studies involving protein acetylation have attracted a great deal of attention. In the present study, we have focussed on the acetylation of histidine and the intrinsic stability of b-ion of oxazolone ring and/or with side chain imidazole bicyclic product. The formation of oxazolone structure may occur when an amino moiety undergoes acetylation reaction and when it is present in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…8 Studies in our laboratory revealed that acetylation of N-terminal histidine-containing peptides leads to the formation of a b 1 ion with an oxazolone structure. 11 Thus, acetylation of peptides generated by trypsin digestion of proteins helps in determining the primary structure of the peptides.…”
Section: Introductionmentioning
confidence: 99%
“…8 Studies in our laboratory revealed that acetylation of N-terminal histidine-containing peptides leads to the formation of a b 1 ion with an oxazolone structure. 11 Thus, acetylation of peptides generated by trypsin digestion of proteins helps in determining the primary structure of the peptides.…”
Section: Introductionmentioning
confidence: 99%